EPIDEMIOLOGICAL ANALYSIS AND SUCCESSFUL MANAGEMENT OF A CANDIDA AURIS OUTBREAK IN A SECONDARY CARE HOSPITAL SETTING IN SAUDI ARABIA; AN OUTBREAK REPORT - Kauser Fathima; Nazia Khan; Faraz, Ali; Syed Yousaf Kazmi; Abdullah Suib al Motery (Journal of Ayub Medical College Abbottabad, 2022)
Candida auris has emerged as a major diagnostic and therapeutic challenge in the hospital environment. C. auris is resistant to many antifungals, making it a newer example of one of the world’s most problematic and feared health threats. We recently confronted a cluster of C. auris cases at our hospital during the spring of 2020.This outbreak investigation took place at the ICU of King Khalid hospital Al Majmaah Saudi Arabia. Considering its potential to cause an outbreak with serious consequences, strict control measures were implemented thus effectively controlling the outbreak.